Shaping the itinerary: Perceived quality of recommendation systems on travel intentions a case study in Vietnam - Dat, Nguyen Van; Tho, Nguyen Van (Edelweiss Applied Science and Technology, 2025)
This study aims to explore how recommendation systems (RS) influence the decision-making process of tourists. By examining the quality of RS, their impact on travel intentions, and the mediating role of satisfaction, the study seeks to model the decision-making process more effectively. Data were collected through a survey of 523 consumers in Vietnam who had previously used RS, employing a convenience sampling method. The survey questionnaire was distributed via email in the form of Google Forms. The study established a conceptual framework and tested the hypotheses using structural equation modeling (SEM). SPSS 26 was employed to assess the reliability of measurement scales, while AMOS 28 was used to evaluate the measurement and structural models. The findings indicate that consumers’ positive perceptions of information quality, system quality, trust, and the usefulness of RS significantly enhance satisfaction and travel intentions. Notably, personalization does not directly influence perceived RS quality but exerts an indirect effect through the usefulness of RS. Satisfaction serves as a critical mediator in the relationship between perceived RS quality and travel intentions, emerging as the most influential factor within the model. This study underscores the effectiveness of decision-making driven by perceived RS quality in the tourism context. These findings provide valuable insights for policymakers and system developers to improve RS quality, thereby attracting tourists, enhancing competitive advantages in the tourism industry.